Comparison of saliva and blood derived cell free RNAs for detecting oral squamous cell carcinoma - Yuan Hu; Manbin Xu; Muyuan Liu; Hanwei Peng (Scientific Reports)
Abstract Oral squamous cell carcinoma (OSCC) is one of the most prevalent cancer types around the world. Although OSCC can be diagnosed or monitored through tissue biopsy, this invasive procedure could cause considerable pain and discomfort to patients. As a preferable alternative, liquid biopsy offers less invasive diagnostics. In our study to enhance OSCC detection, we analyzed cell-free RNA (cfRNA) transcriptomes (mRNA, lncRNA) from blood (plasma) and saliva samples of individuals in three groups: OSCC group, oral benign tumor group, and a normal control group. Our transcriptomic profiling revealed that in the saliva group, CLEC2B was notably upregulated in the OSCC group compared to others, while DAZL, F9, and AC008735.2 were markedly downregulated. However, no OSCC-specific RNAs were identified in the blood (plasma) samples. Furthermore, OSCC group showed a higher neutrophil infiltration and lower B cells, CD4 + T cells (non-regulatory) and regulatory T cell (Tregs) infiltration in oral saliva environment when compared to the control groups. This study suggests that saliva might be a better liquid biopsy medium over blood (plasma) for cfRNA on detecting OSCC. CLEC2B, DAZL, F9, and AC008735.2 in saliva may serve as potential diagnostic liquid biomarkers for OSCC, warranting further investigation.